Investigating the impact of different loading patterns on the permanent deformation behaviour in hot mix asphalt. (10th April 2018) - Motevalizadeh, Seyed Mohsen; Ayar, Pooyan; Motevalizadeh, Seyed Hossein; Yeganeh, Sadegh; Ameri, Mahmoud; bemana, Keyvan
Highlights: Permanent deformation depends on the loading patterns and testing parameters. Power-law model can be used to analyze the permanent deformation characteristic. An increase in rest period and loading duration leads to a higher permanent deformation. Abstract: This research was conducted to evaluate the effect of different loading combinations on the permanent deformation behaviour in asphalt mixtures. Therefore, repeated loading permanent deformation test was performed considering different stress levels, loading durations, rest periods and testing temperatures. The results showed that the slope coefficient of Power-law model has a more influence on permanent deformation compared to intercept. Moreover, rutting zones are sensitive to testing parameters. Rest period could significantly affect the first zone. Nevertheless, secondary zone depends on the loading duration and deviator stress. Eventually, the testing temperature has the greatest influence on the permanent deformation behaviour.